2015
DOI: 10.1016/j.physleta.2015.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of twin boundary effect on deformation of Cu nanopillars

Abstract: Molecular dynamics simulations performed on 110 Cu nanopillars revealed significant difference in the deformation behavior of nanopillars with and without twin boundary. The plastic deformation in single crystal Cu nanopillar without twin boundary was dominated by twinning, whereas the introduction of twin boundary changed the deformation mode from twinning to slip consisting of leading partial followed by trailing partial dislocations. This difference in deformation behavior has been attributed to the formati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 22 publications
5
23
0
1
Order By: Relevance
“…Most of these studies were focused on perfect nanowires, and it is not clear whether the deformation by twinning will continue to occur in the presence of defects such as dislocations and grain boundaries. Recently, it has been shown that the presence of twin boundary in <110> FCC Cu nanopillars changes the deformation mechanism from twinning to slip [19]. In the present study, an attempt has been made to understand the influence of twist boundary on deformation twinning in BCC Fe nanowires.…”
Section: Introductionmentioning
confidence: 92%
“…Most of these studies were focused on perfect nanowires, and it is not clear whether the deformation by twinning will continue to occur in the presence of defects such as dislocations and grain boundaries. Recently, it has been shown that the presence of twin boundary in <110> FCC Cu nanopillars changes the deformation mechanism from twinning to slip [19]. In the present study, an attempt has been made to understand the influence of twist boundary on deformation twinning in BCC Fe nanowires.…”
Section: Introductionmentioning
confidence: 92%
“…The superior mechanical properties of twinned nanopillars have been attributed to unique deformation mechanisms operating in the presence of twin boundaries [11]. In view of this, the materials containing high density of twin boundaries attract huge interest among materials scientists and engineers.Several experimental and molecular dynamics (MD) simulation studies have been performed to understand the influence of twin boundaries on the strength and deformation behaviour in FCC nanopillars/nanowires [12][13][14][15][16].Using MD simulations, Cao et al [12] have shown that in FCC nanopillars, the twin boundaries serve as the strong obstacles for dislocations motion. As a result, the decrease in twin boundary spacing increases the yield strength in orthogonally twinned Cu nanopillars.…”
mentioning
confidence: 99%
“…Further, the strengthening in twinned FCC nanopillars also depends on the size and aspect ratio [14]. In addition to orthogonally twinned FCC nanopillars, the increase in yield stress is also observed in slanted and vertically twinned FCC nanopillars [15,16].Using molecular dynamics simulations and in situ experiments, the deformation mechanisms responsible for superior properties and the associated dislocation-twin boundary interactions have been characterised in FCC nanopillars.Most of the studies reported in the literature have been performed on twinned FCC nanopillars and little attention has been paid to characterise the mechanical behaviour of twinned BCC nanowires/nanopillars. It is well known that the twin boundaries in FCC system coincide with {111} planes, while in BCC systems they coincide with {112} planes [17].…”
mentioning
confidence: 99%
“…However, the influence of twin boundary spacing has not been investigated when the twin boundaries are parallel to the loading direction. Although, under tensile loading, it has been shown that the introduction of longitudinal twin boundary increases the strength of the nanowire compared to its perfect counterpart [13], but the influence of twin boundary spacing is still elusive. Further in twinned nanopillars, the dislocation interactions with twin boundaries needs to be investigated in greater detail.…”
Section: Introductionmentioning
confidence: 99%